German Expressionist Sculpture - Barron, Stephanie; Hirshhorn Museum and Sculpture Garden Smithsonian Institution, Washington; Josef-Haubrich-Kunsthalle, Köln (Los Angeles : Los Angeles County Museum of Art, 1983)
Archipenko, Alexander ; Barlach, Ernst ; Beckmann, Max ; Belling, Rudolf ; Felixmüller ; Freundlich, Otto ; Garbe, Herbert ; Gutfreund, Oto ; Heckel, Erich ; Henning, Paul Rudolf ; Herzog, Oswald ; Hoetger, Bernhard ; Karsch, Joachim ; Kirchner, Ernst Ludwig ; Knappe, Karl ; Kolbe, Georg ; Kollwitz, Käthe ; Lehmbruck, Wilhelm ; Marcks, Gerhard ; Minne, George ; Müller, Albert ; Nolde, Emil ; Pechstein, Max ; Scherer, Hermann, Schiele, Egon ; Schmidt-Rottluff, Karl ; Schwichtenberg, Martel ; Seiwert, Franz ; Sintenis, Renée ; Steger, Milly ; Voll, Christoph ; Wauer, William ; Zadkine, Ossip
German Expressionist Sculpture, Los Angeles County Museum of Art, Los Angeles, October 30, 1983 - January 22, 1984 ; Hirshhorn Museum and Sculpture Garden Smithsonian Institution, Washington DC, April 4 - June 17, 1984 ; Josef-Haubrich Kunsthalle, Köln, July 7 - August 26, 1984
boek